Motivasi Kerja Sama Pembangunan Internasional Indonesia Melalui Indonesian AID di Mozambik dan Kenya - Meylan Zhara Astira; Apriwan; Maryam Jamilah (Hubungan Internasional Universitas Andalas, 2026)
Indonesia as an emerging donor remains committed to increasing foreign aid to Mozambique and Kenya every year. As a fellow developing country, Indonesia establishes development cooperation to support the acceleration of development in the two countries that are implementing the development agenda to achieve stability and sustainability. In addition, the geopolitics of international development between traditional donors such as the United States and China have existed and dominated most of the foreign aid provision in Mozambique and Kenya. This study aims to analyze Indonesia's motivation to conduct international development cooperation through Indonesian AID to Mozambique and Kenya. Indonesia's motivation analyzed using Raymond F. Hopskins' theory of foreign aid motivation, namely global public goods, economic development, domestic coalitions and increased concessions from recipients and using descriptive qualitative methods. This research finds that the Indonesian government's motivation in providing foreign aid to Mozambique and Kenya is related to Indonesia's participation in solving global problems based on normative goals, access to energy resources such as oil, gas and minerals as well as opening up new trade, investment and market opportunities in Mozambique and Kenya, encouragement from state-owned enterprises and targeting Indonesia's continued cooperation with the two countries.